Ketosis Onset Type 2 Diabetes Had Better Islet β-Cell Function and More Serious Insulin Resistance - Hongyun Lu; Fang Hu; Yingjuan Zeng; Lingling Zou; Shunkui Luo; Ying Sun; Hong Liu; Liao Sun (Journal of Diabetes Research)
Diabetic ketosis had been identified as a characteristic of type 1 diabetes mellitus (T1DM), but now emerging evidence has identified that they were diagnosed as T2DM after long time follow up. This case control study was aimed at comparing the clinical characteristic, β-cell function, and insulin resistance of ketosis and nonketotic onset T2DM and providing evidence for treatment selection. 140 cases of newly diagnosed T2DM patients were divided into ketosis (62 cases) and nonketotic onset group (78 cases). After correction of hyperglycemia and ketosis with insulin therapy, plasma C-peptide concentrations were measured at 0, 0.5, 1, 2, and 3 hours after 75 g glucose oral administration. Area under the curve (AUC) of C-peptide was calculated. Homoeostasis model assessment was used to estimate basal β-cell function (HOMA-β) and insulin resistance (HOMA-IR). Our results showed that ketosis onset group had higher prevalence of nonalcoholic fatty liver disease (NAFLD) than nonketotic group (P=0.04). Ketosis onset group had increased plasma C-peptide levels at 0 h, 0.5 h, and 3 h and higher AUC0–0.5, AUC0–1, AUC0–3 (P<0.05). Moreover, this group also had higher HOMA-β and HOMA-IR than nonketotic group (P<0.05). From these data, we concluded that ketosis onset T2DM had better islet β-cell function and more serious insulin resistance than nonketotic onset T2DM.